Pengembangan Modul Bergambar untuk Meningkatkan Pemahaman Materi Jenazah di Kelas VI - Roziqin, Muhamad Khoirur; Khanif, Muhammad Fakhri (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2022)
Learning is a complex process that occurs in everyone throughout his life. The learning process occurs because of the interaction between a person and his environment. One alternative that can be done by teachers so that students can play an active and independent role in developing their knowledge is to use picture modules. Picture modules help teachers and students in implementing the teaching and learning process in schools because the picture media students will be more interested in learning. The purpose of this study was to determine the students' understanding of SDN Pulogedang Jombang in understanding corpse material using a picture module. This type of research is development research (R&D). The product developed is in the form of a picture module of corpse material. The instruments used in this study were an assessment questionnaire by two validators, a student questionnaire assessment sheet and pre-test and post-test questions on learning outcomes. Based on the results of the validation sheet, the illustrated module is classified as suitable for use in learning Islamic Religious Education on corpse material. This can be seen from the results of the validation of the first and second material experts of 3.2. Students' understanding of the use of the illustrated module can be seen from the results of the pre-test and post-test with an average score of 68.45 increasing to 87.06.